ANALYSIS OF GLOBAL TRENDS IN GM MAIZE APPROVALS IN THE PERIOD 2014-2018 - Dorina BONEA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
GM maize events are developed for the benefit of the global population but their approval in each country varies according to consumer acceptance, needs and commercial interests. This study analyzed the number of global approvals (by country and type of approval) for GM maize in the period 2014-2018, based on statistical data collected from the ISAAA-GM Approval Database. Descriptive statistics, regression equations and coefficient of determination were used to identify the trends for these indicators. The results showed that a total of 691 applications were approved in 28 countries. In 2016 was registered the highest number of food, feed and cultivation approvals. South Korea, Argentina, Brazil and Taiwan were the top four countries with the most food approvals, Brazil, South Korea, Argentina and Japan were the top four countries with the most feed approvals, and Argentina, Brazil, Japan and Canada were the top four countries that issued the most cultivation approvals. In developing country the rate of acceptance for GM maize was higher compared to developed countries. Europe issued a total of 26 approvals only for food and feed, with most approvals being issued in 2016.